2022
DOI: 10.4018/978-1-6684-4895-3.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Enablers of Digital Transformation in Small and Medium-Sized Enterprises

Abstract: Recently, digital transformation has attracted much attention of both academics and practitioners. With the advent of digital technologies, small-and-medium-sized enterprises (SMEs) have the capacity to initiate digital transformation initiatives in a similar fashion as the large-sized organizations. The innate characteristics of digital technologies too favor SMEs in initiating digital transformation initiatives. However, the existing the findings on digital transformation in SMEs are limited and remain fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The second refers to the external relationships established by the organization through the supply chain and collaborative partnerships in order to achieve a sustainable digital transformation. Lokuge and Duan [48] employed the same classification for identifying digital transformation enablers, but the content is noticeably distinct. Internal enablers include elements such as sustainable technology capabilities, partnership accessibility, and skilled people, while external enablers include digital technology, the current state of digital competition, and customers' readiness to respond to a business model shaped by digital transformation.…”
Section: Digital Transformation Enablersmentioning
confidence: 99%
“…The second refers to the external relationships established by the organization through the supply chain and collaborative partnerships in order to achieve a sustainable digital transformation. Lokuge and Duan [48] employed the same classification for identifying digital transformation enablers, but the content is noticeably distinct. Internal enablers include elements such as sustainable technology capabilities, partnership accessibility, and skilled people, while external enablers include digital technology, the current state of digital competition, and customers' readiness to respond to a business model shaped by digital transformation.…”
Section: Digital Transformation Enablersmentioning
confidence: 99%
“…As DT enablers may be clothed in different linguistic forms (antecedents, drivers, stimulators, imperatives, just to name a few) (Lokuge and Duan, 2021), the appropriate search terms were constructed. As the first step, the existing literature reviews on DT published in 2019-2021 were searched in Scopus; as Jones (et al, 2021) suggested, it comprises a representative collection of papers on DT.…”
Section: Literature Review For Dt Enablers' Identificationmentioning
confidence: 99%